Perancangan Sistem Aplikasi Layanan Publik Kelurahan Berbasis Web (Studi Kasus Kelurahan Cipayung Kecamatan Ciputat) - Chairul Mudjahid; Husaini Luthfi; Rendi Pratama Juniar; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The rapid growth of technology must be maximized for public services, one of which is the administration of citizen services. Cipayung Sub-District in Ciputat District, as one of the sub-districts implementing public services, has not used the technology to its full potential, mainly because it has not used a data system for resident services. This research aims to design an application system for community services in Cipayung village. This research uses the Waterfall system development procedure. The result of this research is the implementation of the Waterfall procedure starting from the analysis, system requirements, design, development and test phases to create an application system project necessary for the village administration for citizen complaint services in the village of Cipayung, Ciputat.